An Economic Perspective on Abortion Policies - Clara Albrecht; Jennifer Steigmeier (CESifo Forum, 2022)
Abortions are widespread and occur independent of the legal status of abortions. Prohibiting or restricting abortions increases the proportion of unsafe abortions, posing a massive risk on women's health, but does not necessarily reduce the number of abortions being carried out. Economic research contributes to the often heated debates about the legal status of abortions by providing causal evidence for the fact that lacking access to abortion negatively affects the lives of women in many dimensions. Thus, the way abortion policies are designed is of high relevance.
Keywords: 330